2008
DOI: 10.1111/j.1542-474x.2008.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Wavelet Transform Modulus Maxima and Multifractal Detrended Fluctuation Analysis of Heart Rate in Patients with Systolic Dysfunction of Left Ventricle

Abstract: MDFA seems to be more sensitive as compared with WTMM method in differentiation between multifractal properties of the heart rate in healthy subjects and patients with left ventricular systolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 24 publications
1
37
1
2
Order By: Relevance
“…The third method is based on the wavelet transformations (WTs), and has been shown to be a very useful tool for the analysis of a wide variety of nonstationary series. The WTs have been used in many disciplines, ranging from mathematics (Narasimha and Bhattacharyya 2010 and references therein), to environmental science (Heidari Nasab et al 2004;Souza Echer et al 2008), medicine (van Milligen et al 1995;Galaska et al 2008) and geophysics (Grinsted et al 2004;Maraun and Kurths 2004;Ge 2008); for a review see Sahimi (2003).…”
Section: Introductionmentioning
confidence: 99%
“…The third method is based on the wavelet transformations (WTs), and has been shown to be a very useful tool for the analysis of a wide variety of nonstationary series. The WTs have been used in many disciplines, ranging from mathematics (Narasimha and Bhattacharyya 2010 and references therein), to environmental science (Heidari Nasab et al 2004;Souza Echer et al 2008), medicine (van Milligen et al 1995;Galaska et al 2008) and geophysics (Grinsted et al 2004;Maraun and Kurths 2004;Ge 2008); for a review see Sahimi (2003).…”
Section: Introductionmentioning
confidence: 99%
“…cardiac transplantation vs. ventricular tachycardia), evidencing the ANS influences on the cardiac rhythm control. On the other hand, Galaska et al [15] found that the generalized Hurst exponents had a significantly larger range of exponents and the global Hurst exponent was significantly lower in healthy subjects in comparison to patients with systolic dysfunction of left ventricle, when they used MF-DFA algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…The width of f(α) is defined by the index ∆α = α max − α min , which has been used in several studies to evaluate the multifractality degree of f(α) in heart rate dynamics corresponding to healthy and pathologic subjects [9], [10], [14], [15]. Also, the value of the singularity exponent α m for which f(α) is maximum was considered as an index.…”
Section: B Multifractal Analysismentioning
confidence: 99%
“…Finally for "DBC-mes" measure, the results are better than the three other ones, the spectrum width dα is equal to that of the theoretical spectrum ( Figure 7). This result is interesting, because the spectrum width can be used like a discriminative value between two populations [6,17]. Therefore, it is important to have an exact approximation.…”
Section: D Casementioning
confidence: 99%